The radium girls : the scary but true story of the poison that made people glow in the dark - Moore, Kate (Writer and editor) (Sourcebooks eXplore, 2020)
Explores the true story of the women who worked in what at the time was an exciting industry, painting watch dials with radium paint to make them glow in the dark. It was a high paying job, but then these young women began to notice mysterious illness in themselves, and some even started glowing in the dark themselves. Corporations tried to cover it up, but eventually the "Radium Girls" got justice for what these corporations knowingly did to them.